Transparent Touch: Insights From Model Systems on Epidermal Control of Somatosensory Innervation - Yin, Chang; Peterman, Eric; Rasmussen, Jeffrey P.; Parrish, Jay Z. (Frontiers in Cellular Neuroscience, 2021)
Somatosensory neurons (SSNs) densely innervate our largest organ, the skin, and shape our experience of the world, mediating responses to sensory stimuli including touch, pressure, and temperature. Historically, epidermal contributions to somatosensation, including roles in shaping innervation patterns and responses to sensory stimuli, have been understudied. However, recent work demonstrates that epidermal signals dictate patterns of SSN skin innervation through a variety of mechanisms including targeting afferents to the epidermis, providing instructive cues for branching morphogenesis, growth control and structural stability of neurites, and facilitating neurite-neurite interactions. Here, we focus on work from model systems including worms (Caenorhabditis elegans), fruit flies (Drosophila melanogaster), and zebrafish (Danio rerio) in which anatomical and genetic analyses have defined fundamental principles by which epidermal cells govern SSN development.